Pengembangan Model Pembelajaran Project Based Learning (PjBL) dalam Akuntansi Keuangan - Nunuk Suryanti; Sukarni Sukarni; Wiwin Setiawati (Universitas Negeri Surabaya, 2023)
The development of the Project Based Learning (PjBL) learning model in financial accounting courses aims to increase student HOTs in analyzing elements of financial statements. The model used is ADDIE, in the MSME Accounting management course. The model is applied for one semester. The effectiveness test results show that it is very effective, and the practicality results also show a very practical score so that the PjBL development model in financial accounting can be used without revision.